Foreign aid effectiveness in Korea - Debnath, Doyananda (KDI School, 2012)
Korea has come a long way from the conditions it faced few decades ago as one of the poorest and an agrarian countries in the world to become rich and one of the world’s leading industrialized countries. In the early 1960s, Korea’s per capita income was just more than $100, lower than many countries in Africa. But within half a century, Korea transformed itself into an industrialized economy and became the 15th world’s largest economy in the world. Since 2000, Korea has joined the donor club OECD and last year (2010) became the second Asian member of the 24-member of OECD-DAC official. It, therefore, represents a success story of once a major recipient of international economic aid to an aid giver. Giving its background as a former aid recipient and its present position of extending valuable support to other developing countries including sharing of his knowledge and lessons of its successful development, Korea, therefore, has become a beacon for countries around the world. Korea’s remarkable progress gives hope to other developing countries that their situations can be changed to achieve the same status. Lessons from Korea’s miracle, such as its motivated work force, development strategy and aid utilization, aid allocation and performing, strong and closer bilateral relations, and cooperation and collaboration in diverse areas of interest could be the vital for economic development of Bangladesh.
Thesis(Master) --KDI School:Master of Public Policy,2012